Analyzing the Impact of Marketing Mix and Hospital Brand Image on Patient Satisfaction and Loyalty: A Study at XYZ Maternity Hospital - Nur Al Islamiyah, Maryam; Wuisan, Dewi Sri Surya (Eduvest - Journal of Universal Studies, 2024)
This study examines the impact of the marketing mix and hospital brand image on patient satisfaction and loyalty at XYZ Maternity Hospital. As healthcare services face increasing competition, especially among hospitals, marketing strategies such as the 7P marketing mix and brand image play a crucial role in enhancing patient satisfaction and building loyalty. The study uses a quantitative method with 205 postpartum patients as respondents. Data analysis using PLS-SEM reveals that both the marketing mix and hospital brand image have a significant positive effect on patient satisfaction, which in turn strongly influences patient loyalty. These findings underscore the importance of focusing on improving patient-centered services and maintaining a positive hospital image to foster long-term patient loyalty.